2021
DOI: 10.3390/su13041960
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Travel Decision-Making of Europeans: Insights from a Household Survey

Abstract: The purpose of this study is to research the antecedents of the sustainable travel decision-making of European travelers and thereby identify important lessons for the transition towards sustainable travel and tourism. The study is based on data collected through a representative survey, conducted in five European countries, with a sample of n = 5024 respondents. The results of descriptive statistics, EFA (Exploratory Factor Analysis) and FA (Factor Analysis) are presented in order to explore sustainable trave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 99 publications
(128 reference statements)
1
16
1
1
Order By: Relevance
“…This could be a result of the overall high scores for pro-environmental self-image, which has a positive effect on the willingness to reduce flying. However, previous studies have shown that neither environmental awareness (Árnadóttir et al, 2021), nor stated behavior intentions necessarily translate into actual behavior changes (Gehlert et al, 2013;Nikolić et al, 2021). Therefore, it is questionable whether the higher willingness we found in this study is truly indicative of a greater degree of actual behavior change.…”
Section: Discussioncontrasting
confidence: 64%
“…This could be a result of the overall high scores for pro-environmental self-image, which has a positive effect on the willingness to reduce flying. However, previous studies have shown that neither environmental awareness (Árnadóttir et al, 2021), nor stated behavior intentions necessarily translate into actual behavior changes (Gehlert et al, 2013;Nikolić et al, 2021). Therefore, it is questionable whether the higher willingness we found in this study is truly indicative of a greater degree of actual behavior change.…”
Section: Discussioncontrasting
confidence: 64%
“…Blackstock et al [10], for example, state that responsible tourism thinking guides our focus towards actions by individuals who are influenced by ethics and social norms. While ethical principles or shared social norms are not purely individualistic but shared, their impacts on our actions are interpreted and understood as being based on individual behavior and decision-making processes in tourism consumption and production [54]. Indeed, the core idea of responsible tourism refers to tourism with a focus on the ethical and moral responsibility of those engaged in tourism operations, namely tourists and entrepreneurs [10].…”
Section: Responsible Tourismmentioning
confidence: 99%
“…Security problems affect 60% of the countries which are highly dependent on tourism. Aspects such as personal safety, cost, travel time, comfort, and flexibility influence travelers' decisions when choosing a destination for vacationing [18,19]. Regarding personal safety, it has been demonstrated in the literature that the reliability of police services is the sixth most relevant indicator distinguishing developed from developing destinations [20].…”
Section: Introductionmentioning
confidence: 99%